Effect of Meloidogyne incognita population on emergence and seedling characters of cotton - R. A. DHOOT, B. P. KURUNDKAR and (Indian Phytopathology, 2002)
Effect of Meloidogyne incognita juvenile population on cotton (NHH -44) indicated that nematode population has not affected adversely on crop emergence but significantly influenced seedling characters. Nematode population stimulated radicle length but decreased plumule length significantly. Except five juveniles/cc of soil compost, seedling weights were significantly reduced in all other juvenile populations as compared to control. Except vigour index II at 6 days after sowing, vigour indices were significantly reduced.